Modeling personality antecedents and second language self-efficacy constructs with emerging adults in Japan: Domain-specific matching for assessing global competence in applied contexts - Kabir, Russell Sarwar; Kramer, Brandon; Koike, Mayu; Sponseller, Aaron C. (Frontiers in Psychology, 2022)
Previous research found internal and external validity evidence for the construct known as self-efficacy in intercultural communication (SEIC) and suggested that interactions are a source of student growth and engagement in intercultural communication. However, it lacked (1) an analysis of individual differences in personality as antecedents, (2) divergent validity from anxiety variables (i.e., foreign language classroom anxiety; FLCA) and (3) disambiguation from speaking (S-SE) and listening (L-SE) skill-specific self-efficacy types. Here, we conducted structural equation modeling of L2 self-efficacy and anxiety as response variables predicted by the five-factor model of personality in the context of Japanese undergraduate students at three university sites (n = 373), as well as a geographically diverse online survey of emerging adults (n = 1326) throughout Japan. The results of the final model for the nationally representative sample showed that SEIC was predicted by all measured personality factors. In addition, differentially supported paths were observed linking L-SE with Conscientiousness (β = .24) and Extraversion (β = .16), and S-SE with Extraversion (β = .24) and Neuroticism (β = -.12). The fear of failure factor of FLCA was predicted positively by Neuroticism (β = .25) and, surprisingly, Conscientiousness (β =.10), and negatively by Extraversion (β = -.13). Contrary to expectations, relationships to Openness to Experience were only supported for SEIC (β = .17) and S-SE (β = .12). These findings provide specificity matching for L2 self-efficacy domains as empirical advances in the levels of analysis for personality factors and their relationship to applied educational settings, such as global competence assessment within the context of Japan. Implications for cultural influences on self-efficacy assessment and educational practices in language and intercultural learning are discussed.